2015
DOI: 10.3109/19396368.2015.1008071
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status in testis and epididymal sperm parameters after acute and chronic stress by cold-water immersion in the adult rat

Abstract: Stress is associated with detrimental effects on male reproductive function. It is known that stress increases reactive oxygen species (ROS) generation in the male reproductive tract. High ROS levels may be linked to low sperm quality and male infertility. However, it is still not clear if ROS are generated by stress in the testis. The objective of this study was to characterize the role of oxidative stress induced by cold-water immersion stress in the testis of adult male rats and its relation with alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 77 publications
4
31
1
5
Order By: Relevance
“…It has been reported that cold stress increased the production of ROS in animal model and cellular and mitochondrial experiments, respectively (Ali et al 2010;García-Díaz et al 2015;Awad et al 2013). Our results suggest that TRPA1 is mainly involved in the production of ROS via [Ca 2+ ] c elevation pathway induced by cold stress in lung epithelial cell.…”
Section: Production Of Reactive Oxygen Species Is Through the Activatsupporting
confidence: 52%
“…It has been reported that cold stress increased the production of ROS in animal model and cellular and mitochondrial experiments, respectively (Ali et al 2010;García-Díaz et al 2015;Awad et al 2013). Our results suggest that TRPA1 is mainly involved in the production of ROS via [Ca 2+ ] c elevation pathway induced by cold stress in lung epithelial cell.…”
Section: Production Of Reactive Oxygen Species Is Through the Activatsupporting
confidence: 52%
“…Epididymal sperm count was determined as previously described [46]. Epididymis was collected from each group at the end of the 8th week and homogenized in 1 mL of saline.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that the activation of apoptosis in these cells may be related to the activation of the Fas system of procaspase 3 with the loss of mitochondrial membrane potential and the increase in the generation of ROS [3]. As mentioned above, the increase in glucocorticoid concentration may be related to the activation of apoptosis in testicular cells through an increase in ROS generation [48]. Oxidative stress may be related to various etiologies that cause infertility in various species of male mammals, including humans [64].…”
Section: Effect Of Glucocorticoids On Testicular Cellsmentioning
confidence: 99%
“…Cold water immersion stress (15°C for 15 min) applied to rats for 1, 20, 40 and 50 consecutive days has been shown to increase the percentage of seminiferous tubules containing apoptotic germ cells positive for TUNEL (Terminal deoxynucleotidetransferase). In addition, this stressor increases the generation of reactive oxygen species (ROS), such as hydrogen peroxide (H 2 O 2 ), and peroxidation of (H 2 O 2 ) (SOD), catalase (CAT), and glutathione peroxidase (Gpx) [48]. In the testes, H 2 O 2 has the ability to induce apoptosis in testicular cells involving the Fas system and its ligand (FasL) as well as pro-apoptotic proteins: Bax, Bid and Bad [36].…”
Section: Cell Death Activation By Stress In Testicular Germ Cellsmentioning
confidence: 99%